Willing but Unable: Moral Distress and Burnout in Italian Veterinarians Working with Companion and Farm Animals - Emanuela Prato-Previde; Barbara De Mori; Nicoletta Colombo; Annalisa Pelosi (Animals)
Veterinarians face ethical challenges during their careers, but despite evidence of work-related stress and burnout in veterinarians, moral distress has been poorly investigated. Using an online survey, professional experience, moral distress, and burnout were investigated in 704 Italian veterinarians caring for companion animals, farm animals, or both. The reliability of the moral distress questionnaire was optimal, and Factor analysis identified four factors for moral distress: I. Conflict with owner/farmer; II. Relationships with colleagues/superiors; III. Legal context/unsupportive Professional Institutions; IV. Unshared requests for euthanasia. Veterinarians reported rather low levels of moral distress but high levels of work-related stress/anxiety and a decline in empathy over time, mainly toward owners/farmers. More than 50% of veterinarians reported medium/high levels of burnout, and client-related burnout was significantly higher than animal-related burnout. Levels of work-related stress, moral distress, and burnout were higher in women, and experience exerted a protective effect. Moral distress was positively correlated with emotional exhaustion and depersonalization and, to a lesser extent, lower professional fulfillment. The relatively low level of moral distress that emerged in the study needs further investigation, especially considering the high levels of work-related stress and anxiety reported by veterinarians. Women’s greater sensitivity to moral distress and burnout should not be overlooked given the progressive feminization of the veterinary profession worldwide.